The Muslim Contribution to the Formation of United States Identity from the 19th to the 20st Century - Johan Septian Putra; Alkhairi Alkhairi (Regalia Institute, 2026)
This study examines the contributions of early Muslim communities—encompassing enslaved African Muslims and Middle Eastern immigrants from the late 19th to the early 20th century—to the process of shaping the United States as a pluralistic and multicultural nation. Although the presence of Muslims has been recorded since the period of slavery, mainstream American historical narratives have tended to marginalize the significant roles of the Muslim community in the nation’s social, cultural, and spiritual dynamics. Through a historical-qualitative approach and a